2019
DOI: 10.1089/jpm.2018.0528
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis Use in Glioma Patients Treated at a Comprehensive Cancer Center in Florida

Abstract: Background: Glioma is a devastating primary tumor of the central nervous system with difficult-to-manage symptoms. Cannabis products have been postulated to potentially benefit glioma patients. Recent state legalization allowed investigators an opportunity to study glioma patients' adoption of medical marijuana (MM). Objective: Our goals were to: (1) determine the prevalence of marijuana use, both through physician recommendation and self-medication, and (2) evaluate its perceived risks and benefits in glioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…Regardless of the potential benefits on restricting tumor growth, a third of surveyed glioblastoma patients reported using some form of medical marijuana for relief from symptoms ranging from pain and nausea to insomnia and emotional lability, with the vast majority of those reporting symptom improvement [ 110 ]. Similarly, over 67% of patients with primary brain malignancy reported a moderate to significant improvement in their overall condition after 6 months of cannabis use [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the potential benefits on restricting tumor growth, a third of surveyed glioblastoma patients reported using some form of medical marijuana for relief from symptoms ranging from pain and nausea to insomnia and emotional lability, with the vast majority of those reporting symptom improvement [ 110 ]. Similarly, over 67% of patients with primary brain malignancy reported a moderate to significant improvement in their overall condition after 6 months of cannabis use [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…At 6 months, 36.3% of patients reported no more nausea or vomiting, 54.7% claimed symptom improvement, and 9% reported no change ( Bar-Lev Schleider et al, 2018 ). A study by Reblin and colleagues (2019) looked at medical marijuana use in patients with gliomas treated at a comprehensive cancer center in Florida. Thirteen patients used medical marijuana (smoked or ingested THC, CBD only, or THC and CBD oil) for the treatment of nausea; 12 reported symptom relief and 1 reported no effect (Reblin et al, 2019).…”
Section: Overview Of Research Associated With Medical Use In Cancer Patientsmentioning
confidence: 99%
“…25.8% said the symptom disappeared at 6 months, 62.1% reported improvement, and 12.1% reported no change ( Bar-Lev Schleider et al, 2018 ). Reblin and colleagues (2017) reported on 12 patients who used medical marijuana as an appetite stimulant, and all reported symptom relief. In the Minnesota study by Anderson and colleagues (2019), 1,000 patients reported a lack of appetite, and 38.8% achieved a 30% or greater improvement in appetite within 4 months of initiating the use of medical marijuana.…”
Section: Overview Of Research Associated With Medical Use In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the allergic and nutritional epidemiology of glioma showed an inverse association between allergy and gliomas but did not provide any causal relationship between them [ 46 ]. The nutritional epidemiology studies suggested that various food groups and nutrients were associated with glioma risk; the results were inconclusive and not replicable in subsequent research [ 24 , 47 ]. The results of epidemiological analysis also suggested the presence of an inverse association between cancer and certain neurological conditions, mainly age-related neurodegenerative diseases [ 48 ].…”
Section: Epidemiology and Risk Factors Of Gliomamentioning
confidence: 99%